1991
DOI: 10.1111/j.1545-5300.1991.00055.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating FACES III and the Circumplex Model: 2,440 Families

Abstract: Previous evaluations of the Circumplex Model's curvilinear hypothesis using FACES instruments have yielded conflicting results. A review of the different research procedures and samples used in those investigations revealed that none of the studies had samples large and/or heterogenous enough to test the curvilinear hypothesis adequately. The present study evaluates the curvilinear hypothesis of family functioning and the concurrent validity of FACES III with a sample of optimal size (N = 2,440 families) and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(84 citation statements)
references
References 21 publications
2
79
0
1
Order By: Relevance
“…Various studies have found support for the reliability and validity of the Family Cohesion subscale (e.g., Green, Harris, Forte, & Robinson, 1991). Examples of questions include "Family members feel very close to each other" and "We like to do things with just our immediate family."…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have found support for the reliability and validity of the Family Cohesion subscale (e.g., Green, Harris, Forte, & Robinson, 1991). Examples of questions include "Family members feel very close to each other" and "We like to do things with just our immediate family."…”
Section: Methodsmentioning
confidence: 99%
“…For this purpose we adopted the Family Adaptability and Cohesion Evaluation Scale (FACES) of David H. Olson. [4][5][6][7] In addition, we devised a questionnaire on family interactions and the personal situation of the withdrawn person, and used this in a survey of study participants. Family evaluation, family interactions, and personal situations were then compared between those with primary social withdrawal, or other types of social withdrawal, and a group of healthy controls, to identify the characteristics of family relationships in primary social withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…This instrument quickly became one of the standard family assessment tools, and has been used in a large number of projects and clinical evaluations (Olson, 1989). However, in the early 1990s the value of the model began to be questioned (Green et al, 1991), and as approaches such as those based on family narratives have become more popular, the idea of dimensional evaluation has largely disappeared.…”
Section: Discussionmentioning
confidence: 99%
“…However, large scale studies of normal families have tended to report a direct correlation, the higher the score the better the family functioning (Green et al, 1991).…”
Section: Discussionmentioning
confidence: 99%